FUNGSI NASKAH AKADEMIK DALAM PERANCANGAN PERATURAN DAERAH MENURUT UNDANG-UNDANG NO 12 TAHUN 2011 - Dewantara Rata, Kd; Retno Murni, R. A. (Kertha Semaya : Journal Ilmu Hukum, 2013)
Academic paper is the script of research or law study and other research on aspecific problem that can be justified scientifically about setting the issue in a Bill, theDraft Regulation, Province Regulation Draft, or regencies / cities regulation draft as asolution to the problem and legal needs of the community. But in case so many of thoselocal regulations were formed without using an academic paper as the basis of itsformation. Therefore, this article will explain the importance of an academic paper as thebasis of assessment in the establishment of a regional regulation. In addition, this paperalso assess how the role of the community to participate in the preparation of a RegionalRegulation.
Keywords: Academic script, Local Regulation, Research